(untitled) (American Journal of Islam and Society, 2016)
The volume at hand brings together recent advances in and new avenues for the study of both Ithna ‘Ashari and Isma‘ili Shi‘ism in South Asia. As Francis Robinson notes in his introduction, the region’s roughly 60 million Shi‘as were grossly neglected in scholarship until the mid-1980s. Since then, and particularly from the turn of the twenty-first century onward, the situation has changed significantly. Indeed, some of the most interesting and promising recent studies of various historical and contemporary aspects of Shi‘ism in general have focused on those very communities. Justin Jones, one of the spearheads of this development, has acted as co-editor of this important collection of eight thematically highly diverse essays. After Robinson’s overview of the field’s existing literature and the volume’s contents, Sajjad Rizvi tackles a major desideratum in the study of Indian Shi‘i scholarly history by closely examining the life and works of Sayyid Dildar Ali Nasirabadi (d. 1820). A major scholar of his day, as well as the founder of a scholarly dynasty and an instrumental figure in establishing the Usuli tradition in the Shi‘i state of Awadh, his figure and works have, surprisingly, only received attention in the context of Dildar Alis’s polemics against Shah Abd al-Aziz of Delhi (d. 1823) and his critique of Shi‘ism. Reviewing Ali’s severely contested but lastingly influential intellectual attack on Akhbarism, Sufism, Sunnism, and philosophy, all expressed in the context of rising Shi‘i power in late eighteenth-century Awadh, Rizvi aptly highlights the importance of seriously considering major developments in the late pre-colonial period in order to more fully understand the actual and supposed transformations that South Asian Shi‘ism underwent during and beyond colonial rule. Needless to say, this also holds true for the study of other Muslim communities of the nineteenth and twentieth centuries ...